Lesson Learned From The Covid-19 Pandemic: An Examination of Leadership Roles in Telecommunication Company During Crisis - Tatik Prihatini; Sri Iswati; Falih Suaedi (Enrichment : Journal of Management, 2022)
This study aims to investigate the crisis phase and the role of leadership in one of the telecommunications companies in Indonesia that implemented a system of working remotely during the Covid-19 pandemic. This study used a case study methodology with a qualitative approach. Data were collected through in-depth interviews, participant observation, and related documentation. Technical data analysis was carried out through data condensation, data presentation, drawing conclusions, and verifying findings. The results of the study indicate that the leadership role during the Covid-19 pandemic was as follows: pre-crisis phase, peak crisis phase, and post-crisis phase. The pre-crisis phase of the leader guided the team to adapt to the pandemic through planning, information dissemination, and operational coordination. During the crisis phase and the peak of the crisis, the leader played a role in controlling through the provision of motivation, empathy, and inspiration. In the post-crisis phase, the leader's role was to support the recovery process through empowerment, collaboration, and team involvement. The implications of this study are on the importance of the role of leaders who adjust to the phase being faced to be able to bring the organization through difficult times.